2019
DOI: 10.1186/s12955-019-1248-0
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adaptation and validation of the Norwegian version of the swallowing quality of life questionnaire (SWAL-QOL)

Abstract: IntroductionOropharyngeal dysphagia (OD) is a disorder that can have devastating and long lasting effects on a person’s medical, mental and psychosocial well-being, thus negatively impacting quality of life. There is currently no validated dysphagia-specific quality of life instrument in Norway. This project aims to evaluate the psychometric properties of the culturally adapted Norwegian version of SWAL-QOL (Nor-SWAL-QOL).MethodsThe original SWAL-QOL was translated into Norwegian according the international tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This case report paves the way for new physiotherapy interventions for managing complications of cerebellar ataxia. Dysphagia (oropharyngeal dysphagia) manifests as coughing, choking, food sticking, drooling, prolonged mealtimes, and weight loss, with significant long-term psychosocial effects on the quality of life [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This case report paves the way for new physiotherapy interventions for managing complications of cerebellar ataxia. Dysphagia (oropharyngeal dysphagia) manifests as coughing, choking, food sticking, drooling, prolonged mealtimes, and weight loss, with significant long-term psychosocial effects on the quality of life [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of reliable and valid measures in research is essential to provide evidence-based health care [22]. The standardized adaptation process used in the study reported here made it possible to adapt the Delphi DOLBaPP questionnaire specifically for francophones, while preserving the content and structure of the original version.…”
Section: Discussionmentioning
confidence: 99%